HUBUNGAN RELIGIUSITAS DENGAN PSYCHOLOGICAL WELL-BEING PADA ANGGOTA SATPAMWAL DENMA MABES TNI: HUBUNGAN RELIGIUSITAS DENGAN PSYCHOLOGICAL WELL-BEING PADA ANGGOTA SATPAMWAL DENMA MABES TNI - Hamidah, Tjitjik; Gamal, Hendri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
AbstractA lot of workload that must be handled by the Satpamwal Command Guard Denma TNI havecaused excessive work pressure and have an impact on psychological well-being. This studyaims to determine the relationship between religiosity and psychological well-being on thesoldiers of the Satpamwal Denma TNI Headquarters. By using incidental sampling, 45respondents were obtained. Data retrieval uses the scale of religiosity (Glock & Stark, 1996)and the scale of psychological well-being (Ryff & Keyes, 1995) with likert models. Afterbeing tested, there were 41 valid items from 45 items of religiosity scale and 33 valid itemsfrom 40 items on the scale of psychological well-being. The results of data analysis using thebivariate correlation method, concluded that there was a significant relationship with thepositive direction between religiosity and psychological well-being.